Slavery, Sympathy, and White Self-Representation in Dutch Bourgeois Theater of 1800 - Adams, Sarah Josephine (Early Modern Low Countries, 2018)
Unlike the German, French, and particularly Anglo-American cases, the Dutch theatrical imaginings of colonialism, slavery, and race have been largely neglected by scholars of imperial culture. Looking at two early nineteenth-century bourgeois dramas, Stedman (1805) and Kraspoekol (1800), this article examines the complex nexus between slavery, sympathy, and the self-representation of the white middle class in the Netherlands of 1800. As a genre, bourgeois theater cultivated middle-class ideals of compassion, integrity, and benevolence in order to let spectators sympathize with poor, excluded or abused victims. This article explores the constellation of suffering slave characters in relation to the white bourgeois heroes in the plays and to their middle-class audiences. The central argument will be that bourgeois dramaturgy succeeded in conveying antislavery messages, yet primarily delineated and secured a superior white Dutch identity. Consequently, these dramas are considered as segments of the ‘Dutch cultural archive’, defined by Gloria Wekker as a large reservoir of memories, knowledge, and affects that has been crucial to the creation and continuation of white dominance in modern Dutch society.